Nutritional reconstruction in an early modern population: Searching for a relationship between dental microwear and bone element composition - Dąbrowski, Paweł; Kulus, Michał Jerzy; Grzelak, Joanna; Olchowy, Cyprian; Staniowski, Tomasz; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Background: Observing the microwear patterns of the dental crowns enamel surface can provide information on the ingredients and structure of the food consumed, but also on eating habits and lifestyle. Major role in reconstructing the diet and lifestyle of past populations is played by the analysis of alkaline earth metals, such as strontium, barium, zinc and calcium. Ba and Sr are indicators of the consumption of vegetables, plants (cereals and legumes) and marine organisms. This study aims to assess dietary diversity and identify its components based on microscopic techniques and chemical analyses of material from early modern archaeological sites in Wrocław, Poland. Methods: The material consisted of 36 permanent molars and the intrasternal parts of 122 first ribs, collected from 6 Wroclaw early modern cemeteries. Tooth microwear was evaluated on Scanning electron microscopy images, with Microwear 4.02 software. Bone chemical composition (Ca, P, Ba, Sr content) was evaluated with mass spectrometry. Results: Most lines were present on the teeth from St. Mary Magdalene Cemetery, with the lowest average number of lines observed on the teeth from St. Barbara Cemetery. The Ca/P ratios calculated for different sites formed two clusters that allows to distinguish two groups of archaeological sites with different bone preservation status. Number of differences in Ba/Sr, Sr/Ca, Ba/Ca ratios was found between disctinct archaeological sites. A number of correlations were found between the concentration of the chemical elements, but no statistically significant correlation was found between the microwear characteristics and the proportion of the elements studied. Some strong correlations were found between microwear features and the Ca/P ratio. Conclusions: the different values of Sr/Ca, Ba/Ca and Ba/Sr ratios indicate different diets in the different communities. The data obtained indicate a mixed diet, with a relatively high proportion of animal products throughout Wrocław. Conclusions should be treated with caution due to secondary diagenesis. The lack of interdependence between microwear and chemical composition characteristics suggests that the two methods should be considered complementary and not overlapping, as they provide different insights into the diets of past populations. The comparison of microwear between different sites should always take into account secondary diagenesis and the burial environment, as these influence the characteristics of microwear.
CRIS-Team Scopus Importer:2022-01-14
Keywords: Bones; Dental microwear; Diagenesis; Diet reconstruction